Presentation of GIST as jejuno-jejunal intussusception - Anil Kumar; Shiv Shankar Paswan; Anita Paswan; Surya Vikram; Vimal Bhandari (Elsevier, 2018)
Gastrointestinal stromal tumours (GISTs) are rare tumour. It comprises 0.2% of gastrointestinal tumours and only 0.04% of small intestinal tumours. Usually this tumour is found in people in their 60s.These tumours can be found anywhere in the gastrointestinal tract but most commonly found in the stomach (40-60%). Patients with GISTs usually have vague and nonspecific symptoms. We present a 17year-old with complain of abdominal pain, distension, and few episodes of vomiting. All laboratory investigations were normal. The ultrasonography (USG) and computed tomography (CT) were suggestive of jejuno-jejunal intussusception. The patient had emergency exploratory laparotomy with resection of the segment with five cm healthy margin, and end to end anastomosis. Patient was discharged after 4 days and remains well. This case report highlights the rarity of GISTs in the concern of age (17 year old), site (Jejunum) as well as presentation (intussusception).